2015
DOI: 10.1021/acsnano.5b04524
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Metallic Nano-Objects on Crystalline Surfaces by Solution Epitaxial Growth

Abstract: Chemical methods offer the possibility to synthesize a large panel of nanostructures of various materials with promising properties. One of the main limitations to a mass market development of nanostructure based devices is the integration at a moderate cost of nano-objects into smart architectures. Here we develop a general approach by adapting the seed-mediated solution phase synthesis of nanocrystals in order to directly grow them on crystalline thin films. Using a Co precursor, single-crystalline Co nanowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…[15] Inspiredbythis approach, we took advantage of Co particles already immobilizedo nasupport, that is, Co particles of ac onventional FTS catalystp repared by as tandard impregnation method, and used them as seeds on which hcp-cobalt NRs could overgrow from as olution containingm olecular cobalt.I ndeed, someo fu sh ave recently shown that purely hcp Co NRs andn anowires( NWs) can be grown from as olution containing [Co{N(SiMe 3 ) 2 } 2 (thf)],L A, and HDA, on crystallographically oriented metallics ubstrates, which play the role of seeds for the epitaxialC og rowth. [16] These studies have demonstrated that the solution composition dictates the crystallographic structure andt he shape of the Co nanostructures, and this independently of the substrate nature and crystallographic orientation. Indeed,h cp Co NRs/NWshave been obtained in all cases, their growth startinge ither from (111)f cc or (0 001) hcp surfaces of various metallicf ilms, and even on the surface of bulk metals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] Inspiredbythis approach, we took advantage of Co particles already immobilizedo nasupport, that is, Co particles of ac onventional FTS catalystp repared by as tandard impregnation method, and used them as seeds on which hcp-cobalt NRs could overgrow from as olution containingm olecular cobalt.I ndeed, someo fu sh ave recently shown that purely hcp Co NRs andn anowires( NWs) can be grown from as olution containing [Co{N(SiMe 3 ) 2 } 2 (thf)],L A, and HDA, on crystallographically oriented metallics ubstrates, which play the role of seeds for the epitaxialC og rowth. [16] These studies have demonstrated that the solution composition dictates the crystallographic structure andt he shape of the Co nanostructures, and this independently of the substrate nature and crystallographic orientation. Indeed,h cp Co NRs/NWshave been obtained in all cases, their growth startinge ither from (111)f cc or (0 001) hcp surfaces of various metallicf ilms, and even on the surface of bulk metals.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, hcp Co NRs/NWs have been obtained in all cases, their growth starting either from (1 1 1) fcc or (0 0 0 1) hcp surfaces of various metallic films, and even on the surface of bulk metals. Thus, by controlling the solution composition, the Co overgrowth could take place anisotropically on the surface of (1 1 1) fcc or (0 0 0 1) hcp six‐fold symmetry facets of the Co particles of the catalyst, which would play the role of seeds . To validate this approach, we first used a conventional 15 % Co/Al 2 O 3 –SiO 2 catalyst ( S BET =128 m 2 g −1 , pore volume=0.32 mL g −1 , mean pore diameter=10 nm) prepared as described in the Experimental Section, for which the particles presented a broad size distribution (Figure S3 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that a wet-chemistry method that produces well-defined and homogeneously shaped nano-objects in solution can reproduce these nano-objects on a solid support by performing the reaction in the presence of this support. By this method it has been possible to epitaxially grow cobalt nanowires and iron nanocubes on crystallographically oriented metal surfaces, 9,10 as well as on bulk metal foams. 11 It was also shown that the epitaxial relationship between the support and the growing nanostructure determines the orientation of the nanostructure on the support surface, while the composition of the solution determines the nanostructure shape, which corresponds to the same shape obtained in solution in the absence of support, thus, to the same exposed facets.…”
mentioning
confidence: 99%
“…They are obtained by adapting the seed-mediated solution phase synthesis of nanocrystals 7 to grow them epitaxially directly on crystalline thin films. 8 On Pt(111), this method leads to the epitaxial growth of vertical wires with the c-axis of the hexagonal compact (hcp) structure parallel to the NW axis. 9 The Co NWs spontaneously self-assemble into hexagonal arrays of 8 Â 10 12 NWs/in.…”
mentioning
confidence: 99%
“…The array under study consists of metallic NWs of length L ¼ 1000 6 80 nm and diameter D ¼ 6.2 6 0.8 nm. 8 Each NW is naturally covered with organic surfactants. Small angle neutron scattering measurements on air-exposed NWs yield a center-to-center interwire distance of d ¼ 9.6 6 0.5 nm corresponding to a packing fraction P ¼ ðp=2 ffiffi ffi 3 p Þ Â ðD=dÞ 2 ¼ 0:38.…”
mentioning
confidence: 99%